Frail phenotype might herald bone health worsening among end-stage renal disease patients - Chao, Chia-Ter; Huang, Jenq-Wen; Chan, Ding-Cheng; Cohort of Geriatric Nephrology in NTUH (COGENT) study group (PeerJ, 2017)
Background Frailty exhibits a high prevalence in end-stage renal disease (ESRD) patients and is associated with adverse health-related outcomes, including falls and fractures. Available studies do not address whether frailty is associated with temporal changes in BMD. We evaluated this issue by analyzing the follow-up dual energy X-ray absorptiometry (DXA) results in an ESRD cohort. Methods In 2015, we enrolled forty-three ESRD patients, divided into frail, pre-frail, and robust ones based on a validated simple FRAIL scale, all receiving DXA at baseline. After one year of follow-up, survivors received another DXA, and we calculated the absolute and percentage changes in area, bone mineral density (BMD), T-, and Z-scores of lumbar spine and femoral neck (FN) between baseline and follow-up examinations. Results Among all, frail individuals with ESRD had significantly lower average lumbar spine area, lower L4, FN, and total BMD and T-scores, lower FN and total Z-scores than non-frail ones, without differences in gender, body mass index, dialysis duration, and comorbidities. Furthermore, we discovered frail ESRD patients had significantly more prominent decrease in average lumbar spine area, percentage changes in L1 Z-scores and average lumbar spine area, and a trend toward more prominent decrease in L4 area than non-frail ones after one year of follow-up. Conclusions Baseline frailty might be associated with deteriorating bone health, including shrinking L-spine areas and a more rapid decrease in L-spine Z scores, among ESRD patients. This frailty-bone association should be highlighted during our care of frail individuals with ESRD.
Keywords: Bone mass; Osteoporosis; Dialysis; Dual energy X-ray absorptiometry; Frailty; End-stage renal disease; Chronic kidney disease